Multifunctional CuO‐Coated Mesh for Wastewater Treatment: Effective Oil/Water Separation, Organic Contaminants Photodegradation, and Bacterial Photodynamic Inactivation. Issue 22 (25th October 2021) - Meng, Tingting; Zhang, Jianhong; Wang, Huichao; Fu, Nuo; Wang, Mengpei; Li, Weishang; Shi, Ruixin; Peng, Bo; Li, Peng; Deng, Ziwei
Abstract: The complex pollutants in wastewater including insoluble oils, organic dyes, and bacteria, have caused severe environmental problems, which are harmful to ecosystems and human health and are complex and difficult to achieve wastewater purification with one material or single procedure. Herein, a facile, yet environmentally benign strategy is proposed to fabricate a superhydrophilic/underwater superoleophobic CuO‐coated mesh for all‐in‐one wastewater treatment. In this strategy, the hierarchical micro/nanostructured CuO‐coated mesh is fabricated via an oxidation–dehydration process, which simultaneously endows the mesh with superwetting ability, remarkable photocatalytic degradation ability, and excellent photodynamic antibacterial activity. This CuO‐coated mesh first exhibits the special underwater superoleophobicity, superior durability, reusability, and high antifouling capability, which ensures its high separation efficiency for oil/water mixtures. Then, this CuO‐coated mesh is underwater superoleophobic, possessing the remarkable photocatalytic degradation performance of organic dye contaminates in water and excellent photodynamic antibacterial activities against Escherichia coli and Staphylococcus aureus under visible‐light irradiation. As such, it plays a multi‐role in wastewater remedy, significantly simplifying the implementation and saving the cost in practice. This work suggests a promising approach for the design of multi‐functional materials in environmental remedies. Abstract : Multifunctional CuO‐coated mesh is endowed with superwetting ability, remarkable photocatalytic degradation ability, and excellent photodynamic antibacterial activity via an oxidation–dehydration process, which can serve as a versatile platform for all‐in‐one wastewater treatment.